Heat Vision Based Light Automation (International Journal of Scientific Research and Management (IJSRM), 2024)
The Human Detection project utilizing thermal sensors aims to detect individuals or groups in the surrounding environment and respond accordingly. For instance, it can adjust lighting in a room or on a street to accommodate the presence of an individual instead of illuminating everything. Thermal sensors can also detect the presence of people and cars, making street lighting smart and adapting to the lighting situation accordingly. This technology can save up to 70% of energy costs while maintaining safe streets in high-crime areas and creating room for photovoltaic cells. Accurate occupancy tracking and temperature control are crucial in any organization or society, particularly in crowded places like hospitals or malls. To address this issue, we are introducing a data-driven electronic and sensor-based system that can detect the overall environment’s temperature. This system is not a simple machine that gives a single output related to human temperature, but it provides real-time data to detect other parameters for multiple applications.